2009
DOI: 10.1016/j.optmat.2008.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Time-resolved spectroscopy of intrinsic luminescence of Y3Ga5O12 and (LaLu)3Lu2Ga3O12 single crystals

Abstract: a b s t r a c tThe nature of intrinsic luminescence of Y 3 Ga 5 O 12 (YGG) and (LaLu) 3 Lu 2 Ga 3 O 12 (LLGG) single crystals grown from a melt was determined. In the case of a YGG single crystal containing Y Ga antisite defects with a concentration of 0.25-0.275 at.% the intrinsic luminescence was considered as a superposition of luminescence of self-trapped excitons (STE), luminescence of excitons localized near antisite defects (LE(AD) centers) and luminescence caused by a recombination of an electron with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…As for YGG a value of E exc = 5.93 eV, at 8 K, has been reported from which value a band gap of 6.21 eV is obtained, according to eq , in quite good agreement with band gap value reported in the literature for YGG . According to this, by assuming, for YGG, E fa = E g,opt = 5.50 ± 0.05 eV, it is possible to write which can be rearranged as …”
Section: Band Gap Estimation Of Y2o3 and Lu2o3 Polymorphs And Ternary...supporting
confidence: 83%
“…As for YGG a value of E exc = 5.93 eV, at 8 K, has been reported from which value a band gap of 6.21 eV is obtained, according to eq , in quite good agreement with band gap value reported in the literature for YGG . According to this, by assuming, for YGG, E fa = E g,opt = 5.50 ± 0.05 eV, it is possible to write which can be rearranged as …”
Section: Band Gap Estimation Of Y2o3 and Lu2o3 Polymorphs And Ternary...supporting
confidence: 83%
“…The values of the bandgap E g (eV) for the YAGG family were determined using variety of experimental techniques (absorption spectra, optical spectroscopy at LHe, etc. ). ,, We selected one data set and compared it with our results obtained by DFT modeling (Figure ). Several different distributions of Ga over sites were used in calculations: (i) black squares, uniform Ga distribution; (ii) magenta and green, octahedral and tetrahedral Ga occupation, respectively; (iii) blue triangles, Ga distribution from experimental work .…”
Section: Discussionmentioning
confidence: 99%
“…Improved physical properties were also observed for differently doped gadolinium scandium gallium garnets (Gd 3 Sc 2 Ga 3 O 12 , GSGG) [41][42][43]. The results reported in several studies [44][45][46][47] indicated that transition metal-or lanthanide-doped lutetium gallium garnets (Lu 3 Ga 5 O 12 , LuGG) are promising new laser materials, and they are expected to be comparable to the most widely used compound, YAG. In addition, these mixed-metal garnets are potential candidates for deep red light-emitting diodes application, which could be used even for plants and vegetables cultivation [48,49].…”
Section: Introductionmentioning
confidence: 94%